Evaluación de la situación financiera de la empresa Kineletec S.A. en tiempos de pandemia covid-19 Babahoyo periodo 2019-2020 - Arreaga Alcívar, Darwin Marcelo (2021)
Financial analysis is fundamental for companies, because it allows to know information related to the economic and financial situation. For this reason, the objective of the research is to evaluate the behavior of the main financial indicators in times of pandemic of the company Kineletec S.A. The scope of the research is descriptive and the methodology is conformed by the empirical method, supported by the document analysis technique. The types of research applied were field and documentary; while, the sample determined for the financial evaluation consists of the Statements of Financial Position and Results, years 2019 and 2020. A horizontal analysis was applied which determined the following: the current assets account presents a decrease in absolute and relative terms, accounts receivable have a negative variation of 98%; likewise accounts and notes payable with -99% and equity decreased by 96%; while, the results of the horizontal analysis of the income statement determined a considerable decrease in sales, in absolute terms there is a difference of -531,857.10. In addition, the operating costs suffered a positive variation; where the wages and salaries account with the respective social benefits and workers' participation increased by 78%. The analysis of the financial ratios established that the company's current liquidity improved in 2020, due to the amortization of liabilities and the debt ratio decreased from 26% to 9%, where the company sold fixed assets to cancel debt obligations and thus face the economic crisis of the pandemic.